Pengaruh display produk dan kelengkapan produk terhadap keputusan pembelian di Toko Elektronik Kusuma Kecamatan Pakel Kabupaten Tulungagung - Mukti, Widodo Prayoga (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Kusuma Electronic Shop is a retail business selling various electronic devices, such as speakers, electrical components, lamps, etc. Kusuma electronic shop is here to make it easier for consumers to find electronic needs. The various conveniences offered by Kusuma electronic shop support product display and completeness in purchasing decisions. This study aimed to examine the effect of product display and product completeness partially and simultaneously on buying decisions. This research was a quantitative study with variables of product display, product completeness, and buying decisions. To collect the data, questionnaires were distributed to 80 respondents who were consumers of Kusuma electronic stores, using incidental sampling techniques. The data analysis in this study used multiple linear regression analysis. The results of partial hypothesis testing show that product display positively and significantly affects purchasing decisions. In contrast, product completeness positively and significantly affects buying decisions. The results of simultaneous hypothesis testing showed that product display and completeness positively and significantly impact buying decisions. In multiple regression analysis, product completeness results have a more dominant influence on purchasing decisions at the Kusuma electronics store. Kusuma electronics store is expected to improve product arrangement and add product types and brands to diversify the product range. Kusuma must maintain and continue to improve product arrangement and product availability